2010
DOI: 10.1080/00224491003632834
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunction in Women with Diabetes Mellitus

Abstract: Diabetes mellitus (DM) is an increasing health concern throughout the world. DM is categorized as either type 1 (DM-1) or type 2 (DM-2), where DM-1 represents a lack of insulin production, and DM-2 is characterized by a relative lack of insulin (i.e., decreased sensitivity to the effect of insulin). DM has long been considered a risk factor for sexual dysfunction in men and women, although the evidence in women is less clear. This review attempts to give an overview of female sexual dysfunction in women with D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
76
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(91 citation statements)
references
References 76 publications
11
76
1
3
Order By: Relevance
“…19 Over the last few years, evidence has emerged supporting the inclusion of ''distress'' in the definition of FSD; 20 however, the interpretation of the term "distress" can vary according to the woman's perception, from a persistent deterioration of the female psychology to a simple concern. 5 Three classical medical definitions for FSD are generally accepted and have been provided by well recognized medical resources. The ICD-10 classification focuses on physical factors that influence sexual response, 21 the Diagnostic and Statistical Manual (DSM) -IV underlines the emotional and psychological factors involved in FSD, 22 and the most recent classification from the American Foundation of Urological Disease (AFUD) combines the previous classifications with the newest cyclic sexual response model proposed by Basson.…”
Section: Female Sexual Dysfunction: Definition Prevalence and Etiolmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Over the last few years, evidence has emerged supporting the inclusion of ''distress'' in the definition of FSD; 20 however, the interpretation of the term "distress" can vary according to the woman's perception, from a persistent deterioration of the female psychology to a simple concern. 5 Three classical medical definitions for FSD are generally accepted and have been provided by well recognized medical resources. The ICD-10 classification focuses on physical factors that influence sexual response, 21 the Diagnostic and Statistical Manual (DSM) -IV underlines the emotional and psychological factors involved in FSD, 22 and the most recent classification from the American Foundation of Urological Disease (AFUD) combines the previous classifications with the newest cyclic sexual response model proposed by Basson.…”
Section: Female Sexual Dysfunction: Definition Prevalence and Etiolmentioning
confidence: 99%
“…The first mention of this disorder was made in the 10 th century AD when the Persian physician and philosopher Avicenna described the "collapse of sexual functions" in men with diabetes. 5 Numerous presentday studies have shown that men with diabetes are indeed at increased risk for erectile dysfunction, which occurs at an earlier age [6][7][8][9][10] than in non-diabetics and is related to duration of diabetes, poor metabolic control, and the presence of diabetic complications. 11 Sexual dysfunction can be the first sign of the disease and also an indication of the patient's vascular status.…”
Section: Introductionmentioning
confidence: 99%
“…A recent report speculated that before 2030, diabetes would have affected approximately 40% increase of the world population [1]. Also, male reproductive challenges of modern societies reveal that the increased incidence of DM was closely linked with falling birth rates and infertility [2,3]. This could be attributed to the disturbing increase of diabetic men in reproductive age.…”
Section: Introductionmentioning
confidence: 99%
“…Vascular damage and neuropathy may result in decreased genital blood flow, leading to impaired genital arousal response; and 4. Psychosocial factors such as adjustment to the diagnosis of DM, the burden of living with a chronic disease, and depression may impair sexual function (Giraldi and Kristensen, 2010).…”
Section: Effects Of Diabetes Mellitus On Female Fertilitymentioning
confidence: 99%